Hox Genes Studies from the 20th to the 21st Century - Deutsch, Jean S.; SpringerLink (Online service) (New York, NY : Springer New York, 2010)
The purpose of this book is to argue, and to convince those who may not agree, that the Hox genes are indeed so important that their study will not end with the 20th century. The book is divided into three major sections. The first section covers aspects of the regulation of Hox gene expression and the structure and function of the now justifiably well-known homeobox. The second section offers insights and discussions of the sometimes contentious issues of the origin and evolution of the aforementioned Hox complexes. In the third and last section the role of the resident loci in the specification of body plans and meristic identity of the arthropods is presented.
Mechanisms of Activity -- Regulation of Hox Activity: Insights from Protein Motifs -- Cis-Regulation in the Drosophila Bithorax Complex -- Maintenance of Hox Gene Expression Patterns -- Control of Vertebrate Hox Clusters by Remote and Global Cis-Acting Regulatory Sequences -- Evolution of Hox Genes and Complexes -- The Early Evolution of Hox Genes: A Battle of Belief? -- Evolution of Hox Complexes -- The Nematode Story: Hox Gene Loss and Rapid Evolution -- Are the Deuterostome Posterior Hox Genes a Fast-Evolving Class? -- Biological Function -- Hox Genes and the Body Plans of Chelicerates and Pycnogonids -- Hox3/zen and the Evolution of Extraembryonic Epithelia in Insects -- Hox Genes and Brain Development in Drosophila -- Homeosis and Beyond. What Is the Function of the Hox Genes?.
Keywords: Medicine; Medical genetics; Biomedicine; Gene Function; Biomedicine general